Combined analysis of transcriptomics and metabolomics on the cumulative effect of nano-titanium dioxide on mulberry seedlings - Yu, Dongliang; Lu, Qingyu; Wei, Yuting; Hou, Di; Yin, Xingcan; Cai, Kunpei; Qiu, Changyu; Xu, Kaizun (Frontiers in Plant Science, 2023)
Titanium dioxide nanoparticles (TiO2 NPs) are among the most widely used inorganic nanomaterials in industry, environmental governance, medicine and food additives. There are increasing concerns regarding their potential risks to plants and the environment. Mulberry trees are widely grown in China due to their high survival rate, resistance to adversity and ability to aid ecological recovery. Herein, the effects of TiO2 NPs with different concentrations (100, 200, 400 and 800 mg/L) on the growth and physiology of the mulberry tree were systematically evaluated in aspects of physiology, transcriptomics and metabolomics. Results showed that TiO2 NPs could be absorbed by the mulberry sapling root system and be transferred to the plant shoot. This results in the destruction of mulberry sapling root and leaf tissue. Furthermore, the number of chloroplasts and their pigment contents were reduced and the homeostasis of metal ions was disrupted. The toxic effects of TiO2 NPs attenuated the mulberry sapling’s stress resistance, the contents of malondialdehyde in 100 mg/L, 200 mg/L 400 mg/L and 800 mg/L treatment groups increased by 87.70%, 91.36%, 96.57% and 192.19% respectively compared with the control group. The transcriptomic data showed that TiO2 NPs treatment mainly affected the expression of genes related to energy synthesis and transport, protein metabolism, and response to stress. Meanwhile, the results of metabolomics showed that 42 metabolites produced significant differences in mulberry, of which 26 differential metabolites were up-regulated in expression and 16 differential metabolites were down-regulated, mainly including metabolic pathways such as secondary metabolite biosynthesis, citric acid cycle, and tricarboxylic acid cycle, and was not conducive to the seed germination and or growth of the mulberry sapling. This study enriches the understanding of the effects of TiO2 NPs on plants and provides a reference for the comprehensive scientific assessment of the potential risks of nanomaterials on plants.